2011
DOI: 10.1002/ajh.22266
|View full text |Cite
|
Sign up to set email alerts
|

Dapsone salvage therapy for adult patients with immune thrombocytopenia relapsed or refractory to steroid and rituximab

Abstract: Dapsone is an antibacterial sulfonamide with anti-inflammatory property, which showed therapeutic activity in patients with immune thrombocytopenia (ITP) [1][2][3][4][5][6]; the activity in patients who showed refractoriness to rituximab is unknown. We evaluated the effect of dapsone in 20 consecutive adult patients, median age 51 years, with primary ITP previously treated at least with steroids and rituximab. Median baseline platelet count was 19 3 10 9 /L, and the median interval between diagnosis of ITP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
5
32
1
Order By: Relevance
“…For eosinophilic fasciitis , there are impressive case reports about the efficacy of dapsone [142]. Dapsone has been used in several clinical studies in patients with immune thrombocytopenia ( ITP ) in which the disease was refractory against standard therapy [40, 51, 52, 176]. Surprisingly, dapsone showed compelling efficacy both in adults and in children [40].…”
Section: Clinical Use Of Dapsonementioning
confidence: 99%
“…For eosinophilic fasciitis , there are impressive case reports about the efficacy of dapsone [142]. Dapsone has been used in several clinical studies in patients with immune thrombocytopenia ( ITP ) in which the disease was refractory against standard therapy [40, 51, 52, 176]. Surprisingly, dapsone showed compelling efficacy both in adults and in children [40].…”
Section: Clinical Use Of Dapsonementioning
confidence: 99%
“…Several retrospective studies demonstrated that dapsone provides an effective, inexpensive, and well-tolerated alternative for patients with refractory ITP (Table 2) [12131415181920]. …”
Section: Discussionmentioning
confidence: 99%
“…The first use of dapsone during ITP was reported in the 1990's by Durand et al [18], and its efficacy was further confirmed in larger series ( Table 2) [19][20][21][22][23][24][25][26][27].…”
Section: Dapsonementioning
confidence: 94%
“…Once the response is obtained, the drug can be tapered progressively. In rare cases, the response persists after dapsone discontinuation [21,23,25,26]. In cases of relapse, a new response could be achieved by resuming the drug, but sometimes after a long interval [29].…”
Section: Dapsonementioning
confidence: 99%